(untitled) (Damascus University Journal for legal sciences, 2024)
This research looks on the Shari’a ruling on Freezing Banks, explaining the concept of Freezing Banks and their functions, then the ruling on their establishment, in order to reach the Shari’a ruling in their dealings of selling, donating, freezing sperm and ovules and artificial insemination, with an explanation of the opinion of the Islamic Jurisprudence Council about such dealings. The research concluded that it is not permissible to sell, freeze or donate semen for any purpose, because of the sanctity of descent and dynasty related to it. As Freezing for artificial insemination between the spouses during the marriage contract, it is permissible out of necessity.